Thermal irritation of teeth during dental treatment procedures - Su-Jung Kwon; Yoon-Jung Park; Sang-Ho Jun; Jin-Soo Ahn; In-Bog Lee; Byeong-Hoon Cho; Ho-Hyun Son; Deog-Gyu Seo (Korean Academy of Conservative Dentistry, 2013)
While it is reasonably well known that certain dental procedures increase the temperature of the tooth's surface, of greater interest is their potential damaging effect on the pulp and tooth-supporting tissues. Previous studies have investigated the responses of the pulp, periodontal ligament, and alveolar bone to thermal irritation and the temperature at which thermal damage is initiated. There are also many in vitro studies that have measured the temperature increase of the pulp and tooth-supporting tissues during restorative and endodontic procedures. This review article provides an overview of studies measuring temperature increases in tooth structures during several restorative and endodontic procedures, and proposes clinical guidelines for reducing potential thermal hazards to the pulp and supporting tissues.